2019
DOI: 10.1186/s40560-019-0404-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of gait independence after mechanical ventilation in the intensive care unit: a Japanese multicenter retrospective exploratory cohort study

Abstract: PurposeGait independence is one of the most important factors related to returning home from the hospital for patients treated in the intensive care unit (ICU), but the factors affecting gait independence have not been clarified. This study aimed to determine the factors affecting gait independence at hospital discharge using a standardized early mobilization protocol that was shared by participating hospitals.Materials and methodsPatients who entered the ICU from January 2017 to March 2018 were screened. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…As a substitute, the functional status was therefore recorded with the corresponding subdomains of the Barthel Index, which is an ordinal scale incorporating 10 subdomains of the activities in daily life and the most widely used activities of daily living scale ( 24 , 25 ). The points of the subdomains “mobility” and “transfer” of the Barthel Index, each ranging between 0 and 15 (“Mobility-Transfer-Barthel”, MTB) were added and represent the functional capacity and gait independence of the patients with a minimum of 0 points (functionally fully dependent) and a maximum of 30 points (functionally independent) ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…As a substitute, the functional status was therefore recorded with the corresponding subdomains of the Barthel Index, which is an ordinal scale incorporating 10 subdomains of the activities in daily life and the most widely used activities of daily living scale ( 24 , 25 ). The points of the subdomains “mobility” and “transfer” of the Barthel Index, each ranging between 0 and 15 (“Mobility-Transfer-Barthel”, MTB) were added and represent the functional capacity and gait independence of the patients with a minimum of 0 points (functionally fully dependent) and a maximum of 30 points (functionally independent) ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Early mobilization is strongly encouraged due to benefits such as improved functional independence and quality of life after ICU discharge [28]. However, a multicenter study in Brazil showed that the prevalence of patient mobilization in the ICU, especially those on mechanical ventilation, is still very low (2%), with weakness, cardiovascular instability and sedation as the main barriers identified [29].…”
Section: Discussionmentioning
confidence: 99%
“…Gender, the presence of comorbidities, education level, body mass index (BMI), and additional demographic factors were variables commonly considered. The impact of delirium and the acquisition of ICU-aw on recovery during the post-intensive care period were also considered [33]. Taking a biopsychosocial approach, the characteristics of PICS have been characterised into biological, psychological, and social/contextual characteristics.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%